Perlindungan Hak Anak terhadap Iklan Rokok yang Tidak Memperagakan Wujud Rokok - Hwian Christianto (Jurnal Konstitusi, 2016)
The decision of Constitutional-Court No. 6 /PUU – VII / 2009 (about cigarette’s Promoting Limitation) to make the promotion of  cigarette more clear in action, without6  manifesting it as a legal advertisement   (46 verse (3) UU. No. 32, 2002). Although the cigarette advertisement    is not along with the cigarette’s appearance, it still has a huge effect for children. In this circumstance, an attractive debate will rise up between the economic orientation of the cigarette’s entrepreneur and the Children’s Right-Commission purpose. Both of them also get the protection as an expression of constitutional right6 (27 and 28 A, verse (2) UUD 1945). then over here there is an important meaning of Constitutional – Court’s decision No.6 /PUU – VII / 2009, which gives an answer of the law’s issue whether a cigarette advertisement without the appearance, it still also seize the children’s  constitutional  right.